Revisiting the arts as a socially innovative urban development strategy. Issue 3 (3rd March 2020) - Strom, Elizabeth
ABSTRACT: Arts and cultural activities have become an increasingly important aspect of urban and regional development. Can such projects be seen as socially innovative? Socially innovative projects are here understood as those that create new ways of looking at problems, new organisational means for dealing with problems and solutions that go beyond market efficiency. This paper considers arts-based redevelopment projects at regional, municipal and neighbourhood scales. Its focus is on US cities with some examples drawn from Europe. Initiatives to build regional creative economies and creative clusters, and to revitalise buildings and neighbourhoods through cultural activities can be seen as socially innovative, although they can also catalyse market processes that can have deleterious impacts on vulnerable communities.